2023
DOI: 10.1038/s41586-023-05710-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomere-to-mitochondria signalling by ZBP1 mediates replicative crisis

Abstract: Cancers arise through the accumulation of genetic and epigenetic alterations that enable cells to evade telomere-based proliferative barriers and achieve immortality. One such barrier is replicative crisis—an autophagy-dependent program that eliminates checkpoint-deficient cells with unstable telomeres and other cancer-relevant chromosomal aberrations1,2. However, little is known about the molecular events that regulate the onset of this important tumour-suppressive barrier. Here we identified the innate immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 71 publications
4
58
0
Order By: Relevance
“…Interestingly, we did not detect a substantial overlap with regions of G-banding or with high recombination frequencies, negating a number of previous proposals made without experimental support ( Fig S5 ) ( Rich et al, 1984 ). We do observe a marked overlap with subtelomeric regions that was quite unanticipated and is of interest given the role subtelomeric RNAs play in inducing ZBP1-dependent cell death during replicative stress ( Nassour et al, 2023 ).…”
Section: Resultsmentioning
confidence: 81%
“…Interestingly, we did not detect a substantial overlap with regions of G-banding or with high recombination frequencies, negating a number of previous proposals made without experimental support ( Fig S5 ) ( Rich et al, 1984 ). We do observe a marked overlap with subtelomeric regions that was quite unanticipated and is of interest given the role subtelomeric RNAs play in inducing ZBP1-dependent cell death during replicative stress ( Nassour et al, 2023 ).…”
Section: Resultsmentioning
confidence: 81%
“…In human cells, which undergo complete mitotic NE breakdown, telomere fusions that elicit dicentric chromosomes lead to the formation of NE bridges between daughter cells that persist into the next cell cycle; in the subsequent interphase, bridge rupture leads to untimely cytoplasmic exposure with profound consequences for chromosome segregation, including chromothripsis and kataegis. Moreover, as cells harboring telomere fusions traverse mitosis, the presence of telomeric DNA and RNA in the cytoplasm leads to autophagy and activation of innate immune signaling, respectively [59][60][61][62][63][64] . Our work demonstrates that different types of telomeric associations trigger different resolution processes.…”
Section: Conserved Mechanisms Of Dna Processing Across a Continuum Of...mentioning
confidence: 99%
“…Animal studies have also shown that TNF-α levels are increased in animals with shorter telomeres [28]. An in vitro experiment revealed that short telomeres can mediate additional downstream activation of ZBP1(S), via TERRA, to form ZBP1 laments on the mitochondria, thereby promoting the in ammatory cycle [29]. In contrast, other animal experiments have shown that in ammation and oxidative stress signi cantly contribute to renal damage associated with hypertension, and cytokines, such as interferon-γ, TNF-α, and IL-17, affect Na+/H + exchangers in the kidney [16].…”
Section: Discussionmentioning
confidence: 99%